Study of the Microstructure of 20 GL Steel Samples Cut From A WedgeShaped and Side Frame After Volumetric Surface Quenching (Eurasian Scientific Herald, 2022)
This work is devoted to the topic ” Study of the microstructure of 20 GL steel samples cut from a wedge-shaped and side frame after volumetric surface hardening".